1996
DOI: 10.1002/hrdq.3920070106
|View full text |Cite
|
Sign up to set email alerts
|

The effects of affirmative action on the female beneficiary

Abstract: Attention is often focused on the economic and legal aspects of affirmative action rather than the policy's impact on its beneficiaries. The purpose of this article is to integrate the research findings on the effects of preferential treatment on women in organizations and to suggest solutions for some of the problems identified. First, the article explores the impact of preferential treatment on other people's perceptions of the female beneficiary and on the way the beneficiary views herself and the employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Thus, if affirmative action policies are to have a positive impact on women's organizational commitment, it is important that these policies be framed carefully. It should be made clear that such policies are designed to address the past effects of discrimination and increase minority representation and not to encourage an underqualified workforce (Taylor-Carter et al, 1996).…”
Section: Affirmative Actionmentioning
confidence: 99%
“…Thus, if affirmative action policies are to have a positive impact on women's organizational commitment, it is important that these policies be framed carefully. It should be made clear that such policies are designed to address the past effects of discrimination and increase minority representation and not to encourage an underqualified workforce (Taylor-Carter et al, 1996).…”
Section: Affirmative Actionmentioning
confidence: 99%
“…Reactions to perceived beneficiaries of AA are recurrent in the literature (see Heilman, McCullough, & Gilbert, 1996; Kravitz et al., 1997; Taylor‐Carter, Doverspike, & Cook, 1996). Although the literature on beneficiaries of AA has explored this issue in relation to African Americans (see Kravitz et al., 1997) and women (e.g., Heilman, 1996; Heilman & Alcott, 2001; Heilman, Simon, & Repper, 1987; Summers, 1991), perceptions of Asian Americans as targets of AA have been relatively unexplored.…”
Section: Affirmative Actionmentioning
confidence: 99%
“…The International Labor Organization (1995) projects that in three decades the number of retirees could severely influence the economic health of the West. Although some HR development literature investigates the effects of workplace programs on new employees (Holton, 1996) and women (Wentling, 1996;Taylor-Carter, Doverspike, and Cook, 1996), little attention is focused on the older adult in the work setting. Two decades ago, Sheppard and Rix (1977) forecast the changing nature of the workplace and suggested that "it may make sense for employees and government to start now to promote those measures that ensure the continued utilization of older workers in the labor force.…”
mentioning
confidence: 99%